Phylogeny of species formerly assigned to the genus Archocentrus (Perciformes: Cichlidae) - Schmitter-Soto, Juan J. (Zootaxa, 2007)
A phylogeny for 28 cichlid species that have been included in or near the same clade as Archocentrus centrarchus (type species of the genus) in previous phylogenetic analyses is presented, based on 98 morphological characters (osteology, gutcoiling pattern, pigmentation, squamation, meristics, and others), plus one cytogenetic character. Monophyly is supported for Archocentrus sensu stricto, Cryptoheros, Hypsophrys, Amatitlania, and Rocio; the relationships among these genera are not resolved. The three subgenera of Cryptoheros are also supported; Cr. panamensis is the sister group of the rest of the species in the genus. Within Cryptoheros (Cryptoheros), Cr. chetumalensis is the sister group of the clade Cr. spilurus + Cr. cutteri. Within Amatitlania the pattern is: (Am. coatepeque (Am. nigrofasciata (Am. siquia + Am. kanna))).